The architecture design of the wearable health monitoring system based on internet of things technology. (2015) - Wang, Xiaohui
Ageing societies will have to rely increasingly on wearable health monitoring systems to monitor and protect health of the aged in real time. This paper considers that the architecture of the wearable health monitoring system is mainly composed by wearable sensor system, network transmission system and the information processing system on the basis of the three-layer architecture of the internet of things. The data collected by wearable sensor systems would be transmitted through Bluetooth technology to a gateway for providing real-time monitoring. In the family life scope, home computer is usually selected as the home gateway. And when we are out, we can choose intelligent mobile phone as the mobile gateway. The physiological information and data acquired through network are transmitted in real time to the database server. As emerging technologies such as the internet of things are gradually applied to medical monitoring, the wearable health monitoring system will develop into an intelligent, networked and multi-functional one in the future.